Lessons Learned from Teaching in Person Cadaveric Anatomy During the COVID‐19 Pandemic - Davis, Vanessa (FASEB J, 2021)
In March 2020, TTUHSC opened a new 20,000sf Institute of Anatomical Sciences for human gross anatomy. When the COVID‐19 pandemic struck and many schools shifted from in person to online teaching, we hypothesized that if safety measures were used, in person cadaveric anatomy could be safely taught without a decrease in student performance. To test this, we reduced onsite attendance to less than 25% of room capacity. Masks were required at all times and students were instructed to social distance. Six students were assigned per cadaver, but only two students dissected at a time. The other four students reviewed and completed dissections and/or reviewed in groups of two at other allotted times. Thus, students dissected only every third lab. Dissection and lab review attendance was mandatory and students were nearly 100% compliant. Teaching assistants recorded dissected prosections reviews, and these videos were uploaded to password protected course files for independent learning. Students were provided iPads in the laboratory and access to three software packages for use on and off site. All students had access to multiple formative quizzes and exams, and three new online practice practical exams were created. To help reduce testing anxiety, a pass/fail system replaced categorical grading. However, all written and practical exams were conducted on site and in person. At TTUHSC, we have developed an exam question database to track historical student performance including a 25‐question optional pre‐block practice exam used to assess incoming student anatomical aptitude. In 2020, 90% of incoming students (93% in 2019) took the pre‐block exam and scored an average of 28% (24% in 2019). In 2020, despite vastly different content delivery approaches (>80% of lectures were on Zoom) and reduced in‐person dissection requirements, students modestly outperformed their 2019 counterparts. Overall exam averages were 89% in 2020 compared to 87% in 2019. If a categorical system was in place, 66% of students would have earned Honors or High Pass in 2020 compared to 61% in 2019. Our formative assessments were highly predictive of summative exam performance, and students reported that they reduced exam stress. Furthermore, summative exam averages correlated strongly with NBME performance (p<0.0001, r(2)=0.63). TTUHSC medical students estimated that a majority of their peers at other medical schools did not have any in person dissection in 2020. Our students ranked in person laboratory dissection as the most useful learning activity, 88% reported that our COVID‐19 preparations were very good to outstanding, and 97% were satisfied with the quality of their anatomy education. We conclude that 1) When using appropriate precautions, in person cadaveric anatomy can be taught safely during a pandemic; 2) cadaveric dissection is essential for mastery of anatomical concepts; and 3) coupling online learning modalities with rigorous formative assessments prevented a modest reduction in cadaveric dissection opportunities from negatively impacting student performance.